Factors Influencing Employee Professionalism In The Medium Tax Office Sidoarjo - Ari Dwi Aryanti; Pompong B. Setiadi; Sri Rahayu (International Publisher (YAPENBI), 2022)
This study examines what are the factors that influence employee professionalism. These factors consist of workload, employee career development, job enrichment, and communication on employee professionalism at work. The sample in this study were 104 employees at the Medium Tax Office Sidoarjo. The analytical tool used is multiple linear regression. The results of the study show that simultaneously the variables workload, employee career development, job enrichment, and communication have an effect on employee professionalism, while partially the workload variables, employee career development, job enrichment, and communication all have a significant effect on employee professionalism in the Medium Tax Office Sidoarjo. As well as the most dominant variable in its influence on employee professionalism is the communication variable.